Impact of age on the obesity paradox in acute coronary syndrome: a nationwide analysis. (25th November 2020) - Narasimhan, B; Ho, K; Wu, L; Amreia, M; Isath, A; Bhatia, K; Shah, A; Kantharia, B
Abstract: Background: The obesity paradox – indicating improved short term mortality in obese individuals has been widely explored in a number of cardiovascular conditions. However, its validity in an elderly population and the possible physiological impact of aging on this phenomenon in Acute Coronary syndrome (ACS) remain unclear. In this study, we aim to determine the relationship between obesity and in-hospital mortality, morbidity, and health care resource utilization in this cohort of patients. Methods: A retrospective study was conducted using the AHRQ-HCUP National Inpatient Sample for the year 2014. Elderly adults (≥65 years) with a principal diagnosis of ACS and a secondary diagnosis of obesity were identified using ICD-9 diagnosis codes as described in the literature. The primary outcome of in-hospital mortality and secondary outcomes like length of hospital stay (LOS), and total hospitalization costs were analyzed. Propensity score (PS) using the next neighbor method without replacement with 1:1 matching was utilized to adjust for confounders. Independent risk factors for mortality were identified using a multivariate logistic regression model. Results: In total, 1, 137, 108 hospital admissions with a primary diagnosis of ACS were identified, of which 7.46% were obese. In-hospital morality during the index admission was lower among obese patients with ACS compared to non-obese patients (4.62 vs 6.87%, p<0.001) with significantly lower 30-day readmission rates as well (p<0.001). However, in-hospital mortality rates during readmission were statistically equivalent between the obese and non-obese groups (5.6 vs 8.3%, p=0.72). LOS during the index admission was longer for obese patients (6.39 vs 5.36 days, p=0.65) but equivalent to non-obese patients during subsequent readmissions (p=0.12). The total cost of these admissions was significantly more in the obese cohort as well (p<0.001). Conclusion: In this study, obese elderly patients admitted with ACS were found to have significantly reduced in-hospital mortality and 30-day readmission rates when compared to non-obese patients - reinforcing the obesity paradox independent of patient age. Funding Acknowledgement: Type of funding source: None